Twice in a lifetime - Perry, Marta; Copyright Paperback Collection (Library of Congress) (New York : Steeple Hill Books, 2009)
When her family calls brokenhearted Georgia Lee Bodine home to Charleston, she knows there's trouble. Her beloved grandmother hired some fancy lawyer to carry out eccentric requests--and unearth an old family secret. Georgia plans to send Matthew Harper packing until she discovers how much the widowed father cares about her grandmother. And that his heart is even more deeply guarded than her own. As they work together on the Bodine history, they uncover a surprise about themselves: that love can strike twice in a lifetime.--Publisher description.
"Inspirational romance"--Spine.
Keywords: Grandmothers -- Fiction; Single fathers -- Fiction; Widowers -- Fiction; Man-woman relationships -- Fiction; Love stories; Religious fiction